2022
DOI: 10.3389/fnut.2022.923377
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Transcriptomic Profiling Reveals Diet-Related Alterations of Metabolism in Metabolic Disordered Mice

Abstract: Metabolic disorders are the prelude of metabolic diseases, which are mainly due to the high-energy intake and genetic contribution. High-fat diet (HFD) or high-sucrose diet is widely used for inducing metabolic disorders characterized by increased body weight, insulin resistance, hepatic steatosis, and alteration of gut microbiome. However, the triangle relationship among diets, gut microbiome, and host metabolism is poorly understood. In our study, we investigated the dynamic changes in gut microbiota, and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 75 publications
2
7
0
Order By: Relevance
“…First of all, the Unweighted UniFrac principal coordinate analysis (PCoA) showed that HFD groups had dramatically different patterns of gut microbiota with Con and HSD groups. Con and HSD groups clustered together based on PCoA and hierarchical clustering tree analysis (Figure a,b), suggesting that the gut microbial composition was similar between the HSD and Con groups rather than the HFD group, which is consistent with previous reports . In addition, HFD reduced Chao and Shannon index, with no difference between Con and HSD, suggesting HSD had no effect on bacterial richness and evenness (Figure c).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…First of all, the Unweighted UniFrac principal coordinate analysis (PCoA) showed that HFD groups had dramatically different patterns of gut microbiota with Con and HSD groups. Con and HSD groups clustered together based on PCoA and hierarchical clustering tree analysis (Figure a,b), suggesting that the gut microbial composition was similar between the HSD and Con groups rather than the HFD group, which is consistent with previous reports . In addition, HFD reduced Chao and Shannon index, with no difference between Con and HSD, suggesting HSD had no effect on bacterial richness and evenness (Figure c).…”
Section: Resultssupporting
confidence: 88%
“…The genomic DNA extraction and processing, as well as the quality control of raw sequencing data, were conducted in accordance with previous study. 18 Total bacterial genomic DNA samples were obtained from cecal content. Subsequently, PCR amplification of the bacterial 16S rRNA gene V3−V4 region was executed using the universal primers 338F (ACTCCTACGGGAGGCAGCAG) and 806R (GGACTA-CHVGGGTWTCTAAT).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research showed that HFD feeding significantly pressed fatty acid degradation pathway and primary bile acid synthesis pathway in transcriptomic analysis, which is consistent with our previous results. 40 Lipids, particularly LDL-C, represent a significant risk factor for the onset for atherosclerosis, cardiovascular diseases and their complications. 41 As such, the pathways of lipid and atherosclerosis are intricately intertwined with lipid metabolism.…”
Section: Papermentioning
confidence: 99%